Limitations of the human chorionic gonadotropin hCG assay in the diagnosis of gestational trophoblastic disease - Rusman, Zety Wizana; C. Thambiah, Subashini; Samsudin, Intan Nureslyna; Anas, Siti Sharina; Staneshwar, Pavai (Faculty of Medicine and Health Sciences, 2022)
A 31-year-old lady presented with abnormal vaginal bleeding during her first trimester of pregnancy. Based on the ultrasound findings and the decreasing hCG trend (from 1040 mIU/mL to 759 mIU/mL), a diagnosis of missed miscarriage was made. A week later, the patient presented with heavy vaginal bleeding. Ultrasound findings showed classic snowstorm appearance suggestive of complete hydatidiform mole. The serum hCG level however, was 357 mIU/mL. In a case of hydatiform mole with inappropriately low hCG, analytical interference was suspected. Postdilution serum hCG of 5,775,000 mIU/mL confirmed the presence of hook effect in a two-site hCG immunoassay. Discordance between serum hCG and clinical findings should be actively investigated by the laboratory to prevent delay in diagnosis and treatment. This case also highlights the need for clinicians to be aware of the hCG assay used in their hospital’s laboratory so that they may recognise false negative hCG results